RETRACTED: Selection of technical components of Micro HPP - Salomov Uktam; Kuchkarov Akmal; Urishev Omad; Mamatov Olmosbek (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001